Vegetation shadow casts impact remotely sensed reflectance from permafrost thaw ponds in the subarctic forest-tundra zone - Freitas, Pedro (2022)
Thermokarst lakes and ponds are a common landscape feature resulting from permafrost thaw, but their intense greenhouse gas emissions are still poorly constrained as a feedback mechanism for global warming because of their diversity, abundance, and remoteness. Thermokarst waterbodies may be small and optically diverse, posing specifc challenges for optical remote sensing regarding detection, classifcation, and monitoring. This is especially relevant when accounting for external factors that afect water refectance, such as scattering and vegetation shadow casts. In this study, we evaluated the efects of shadowing across optically diverse waterbodies located in the forest–tundra zone of northern Canada. We used ultra-high spatial resolution multispectral data and digital surface models obtained from unmanned aerial systems for modeling and analyzing shadow efects on water refectance at Earth Observation satellite overpass time. Our results show that shadowing causes variations in refectance, reducing the usable area of remotely sensed pixels for waterbody analysis in small lakes and ponds. The efects were greater on brighter and turbid inorganic thermokarst lakes embedded in post-glacial silt–clay marine deposits and littoral sands, where the mean refectance decrease was from -51 to -70%, depending on the wavelength. These efects were also dependent on lake shape and vegetation height and were amplifed in the cold season due to low solar elevations. Remote sensing will increasingly play a key role in assessing thermokarst lake responses and feedbacks to global change, and this study shows the magnitude and sources of optical variations caused by shading that need to be considered in future analyses.